Furans and other volatile compounds in ground roasted and espresso coffee using headspace solid-phase microextraction: Effect of roasting speed - Petisca, Catarina; Pérez-Palacios, Trinidad; Farah, Adriana; Pinho, Olívia; Ferreira, Isabel M.P.L.V.O. (Food and bioproducts processing, 2013)
► HE-SPME-GC/MS of furanic compounds and other volatiles in ground and espresso coffee. ► Pyrazines and ketones were higher in ground coffee than in espresso. ► Furans and pyrroles increased in espresso when compared with ground coffee. ► High roast speed increased 2-furfural and 5-methyl furfural in espresso coffee. ► Roasting parameters influenced volatile and furanic compounds composition of coffee brews. The profile of major classes of furanic compounds, as well as other volatile compounds, was evaluated by headspace solid-phase microextraction GC/MS in Arabica ground coffee roasted at three speeds, and in their respective espresso coffees. A total of 113 and 105 volatile compounds were respectively identified in ground coffee and espresso coffee. They were clustered in the following chemical classes: furans, pyrroles, pyridines, pyrazines, ketones, hydrocarbons, aldehydes and others. Results from Principal Component Analysis (PCA) using the data of major volatile class as variables showed that the levels (expressed as relative percentage of total peak area) of furans and pyrroles were higher in espresso samples, whereas those of pyrazines and ketones were higher in ground samples. Slow roasting speed favoured pyridines formation, while medium and fast roasting speed favoured ketones formation. The most representative furanic compound in ground samples was furfuryl alcohol, followed by furfuryl acetate, 2-furfural, 2-methylfuran and 5-methylfurfural. In espresso samples, the levels of 2-methylfuran, 2-furfural, furfuryl formate, 5-methylfurfural and furfuryl acetate were largely increased while the proportion of furfuryl alcohol was strongly reduced in comparison to ground coffee. High roast speed increased formation of 2-furfural and 5-methyl furfural in espresso coffee.